2020
DOI: 10.1002/aocs.12458
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Osage Orange Extract in Soybean Oil and Fish Oil during Storage

Abstract: The food industry is seeking natural antioxidants for edible oils that have comparable activity to synthetic counterparts. In this study, Osage orange extract (OOE) rich in osajin (42.9%) and pomiferin (30.0%) was obtained after hexane extraction of the fruit, and its antioxidant activity was examined in stripped soybean oil (SBO) and fish oil (FO), in which antioxidants and polar compounds were removed. The antioxidant activity of OOE was compared with commercial natural antioxidants (i.e., rosemary extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Lipid peroxidation was measured by determining the levels of malondialdehyde (MDA) [38]. Similarly, Hwang et al showed the antioxidant activity of the large quantity of pomiferin present in Osage orange extract [39]. Interestingly, neither diplacone nor morusin demonstrated any antioxidant effect in the CAA assay, as seen in Figure 3.…”
Section: Cellular Antioxidant Activity (Caa) Assaymentioning
confidence: 91%
“…Lipid peroxidation was measured by determining the levels of malondialdehyde (MDA) [38]. Similarly, Hwang et al showed the antioxidant activity of the large quantity of pomiferin present in Osage orange extract [39]. Interestingly, neither diplacone nor morusin demonstrated any antioxidant effect in the CAA assay, as seen in Figure 3.…”
Section: Cellular Antioxidant Activity (Caa) Assaymentioning
confidence: 91%
“…A study in which osajin (42.9%) and pomiferin (30%) extracted from MP fruits were tested on soybean and fish oils, from which antioxidants and polar components were removed, showed higher antioxidant activity in both oils compared to other commercially available natural antioxidants. Therefore, this study suggests that M. pomifera extracts could be used as an antioxidant for edible oils, though additional safety tests are necessary before implementation (Hwang et al 2021). Antioxidant activity has also been demonstrated by isolating pomiferin from MP fruits, this molecule being often isolated together with a small amount of osajin, which structurally resembles pomiferin but lacks an aromatic hydroxyl group.…”
Section: Discussionmentioning
confidence: 93%
“…Osajin is one of the isoflavones from A. vera, which acts as an antidiabetic agent [26]. Osajin administration was able to improve blood glucose levels, insulin levels, and C-peptide numbers towards normal values in diabetic model mice [27].…”
Section: The Effectiveness Of Bioactive Compound Inmentioning
confidence: 99%